HASIL BELAJAR KETERAMPILAN PROSES SISWA MELALUI PENERAPAN STARTER EXPERIMENT APPROACH PADA MATERI POKOK HUKUM NEWTON KELAS VIII SMP NEGERI SATU ATAP TAMBANG - Nurhidayatul Jannah; Mitri Irianti; Muhammad Sahal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study is aims at describe learning outcomes student process skills through application starter experiment approach on the subject matter of Newton's law in class VIII Junior High School Satu Atap Tambang. Subjects numbered 33 student of class VIII Junior High School Satu Atap Tambang consisting of 15 male and 18 female. This research is a form of pre-experimental design the one-shot case study. The research instrument used in the form of process skill achievement test. Results learning process skills studied cover the aspects of skill to experiment, observe the skills, the skills of hypothesis, concluding skills and skills acquired implementing the concept. The results showed an average result of learning skills of the students 73.42% in both categories. Thus, the implementation of Starter Experiment Approach effectiveapplied to practice the skills of the class VIII Junior High School Satu Atap Tambang.Keywords : Starter Experiment Approach, process skills, Newton's Law.